"Reinventing NOG's and rethinking alternatives in the Andes", por Anthony Rebbington: The Annals of the American Academy of Political & Social Science, November 1997, vol. 554, p.117 - Gorgal, Diego Pablo (1998)
Fil: Gorgal, Diego Pablo. Pontificia Universidad Católica Argentina; Argentina